Human voltage-gated sodium channel mutations that cause inherited neuronal and muscle channelopathies increase resurgent sodium currents - Jarecki, Brian W. (American Society for Clinical Investigation, 2009)
Inherited mutations in voltage-gated sodium channels (VGSCs; or Nav) cause many disorders of excitability, including epilepsy, chronic pain, myotonia, and cardiac arrhythmias. Understanding the functional consequences of the disease-causing mutations is likely to provide invaluable insight into the roles that VGSCs play in normal and abnormal excitability. Here, we sought to test the hypothesis that disease-causing mutations lead to increased resurgent currents, unusual sodium currents that have not previously been implicated in disorders of excitability. We demonstrated that a paroxysmal extreme pain disorder (PEPD) mutation in the human peripheral neuronal sodium channel Nav1.7, a paramyotonia congenita (PMC) mutation in the human skeletal muscle sodium channel Nav1.4, and a long-QT3/SIDS mutation in the human cardiac sodium channel Nav1.5 all substantially increased the amplitude of resurgent sodium currents in an optimized adult rat–derived dorsal root ganglion neuronal expression system. Computer simulations indicated that resurgent currents associated with the Nav1.7 mutation could induce high-frequency action potential firing in nociceptive neurons and that resurgent currents associated with the Nav1.5 mutation could broaden the action potential in cardiac myocytes. These effects are consistent with the pathophysiology associated with the respective channelopathies. Our results indicate that resurgent currents are associated with multiple channelopathies and are likely to be important contributors to neuronal and muscle disorders of excitability.